1986
DOI: 10.1002/zaac.19865330215
|View full text |Cite
|
Sign up to set email alerts
|

Phasendiagramm des quasibinären Systems NiCr2S4–NiGa2S4, Kristallstruktur des NiGa2S4

Abstract: Das quaternäre System NiCr2–2xGa2xS4 wurde mit Hilfe von Röntgenguinier‐Aufnahmen abgeschreckter Präparate untersucht und die Kristallstruktur der bisher nicht beschriebenen Verbindung NiGa2S4 anhand von Einkristalldaten bestimmt. NiGa2S4 kristallisiert in der trigonalen Raumgruppe P3m1 mit Z = 1 sowie a = 362,49(2) und c = 1199,56(5) pm in einer hexagonal dichtesten Packung des Schwefels mit den Nickel‐ und Galliumionen in je 1/4 der vorhandenen Oktaeder‐ und Tetraederlücken (FeGa2S4‐Typ). Der S;S‐Abstand de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Table 1 summarizes results of the lattice constant refinement for the pure NiGa 2 S 4 polycrystalline sample including values of hkl, both observed and calculated d, and 2y. The obtained lattice constants, a ¼ 0.362502(14) nm, c ¼ 1.199743(55) nm and V ¼ 0.136533(13) nm 3 agree well with the results from the previous report, a ¼ 0.36249(2) and c ¼ 1.19956(5) nm [4].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Table 1 summarizes results of the lattice constant refinement for the pure NiGa 2 S 4 polycrystalline sample including values of hkl, both observed and calculated d, and 2y. The obtained lattice constants, a ¼ 0.362502(14) nm, c ¼ 1.199743(55) nm and V ¼ 0.136533(13) nm 3 agree well with the results from the previous report, a ¼ 0.36249(2) and c ¼ 1.19956(5) nm [4].…”
Section: Resultssupporting
confidence: 91%
“…Reflecting the layered structure of these materials, the crystals cleave easily parallel to their large plane which is found to be perpendicular to the c axis. Structural characters of this single crystal were investigated by using 4-circle XRD measurements [9], and it is found that structural information, such as its symmetry, atomic coordination and lattice constants, is fully consistent with the previous report [4]. XRD analysis for polycrystalline samples at room temperature indicates single phases with the same trigonal structure as that of NiGa 2 S 4 at least up to x ¼ 0.1 for Mn, x ¼ 1 for Fe, x ¼ 0.5 for Co and x ¼ 0.3 for Zn.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In comparison with the structures of FeGa 2 S 4 (Dogguy-Smiri, NguyenHuy Dung and Pardo, 1980), NiGa 2 S 4 (Lutz, Buchmeier and Siwert, 1986) und CoGaInS 4 (Haeuseler, Stork and Cordes) which all crystallize in the same structure type, the distortions of the octahedra as well as the tetrahedra are smallest in the case of MnGa 14 Sc 06 S 4 .…”
Section: Resultsmentioning
confidence: 92%
“…24 and scaled to the bond lengths using Harrison's law. The trigonal distortion of the octahedral cluster 23,24 is also included in the calculation ͓see Fig. 5͑c͔͒.…”
Section: B Model Hartree-fock Calculation Of Fes 2 and Nis 2 Triangumentioning
confidence: 99%